An interacting network of T-box genes directs gene expression and fate in the zebrafish mesoderm - Goering, Lisa M. (National Academy of Sciences, 2003)
T-box genes encode transcription factors that play critical roles in generating the vertebrate body plan. In many developmental fields, multiple T-box genes are expressed in overlapping domains, establishing broad regions in which different combinations of T-box genes are coexpressed. Here we demonstrate that three T-box genes expressed in the zebrafish mesoderm, no tail, spadetail, and tbx6, operate as a network of interacting genes to regulate region-specific gene expression and developmental fate. Loss-of-function and gain-of-function genetic analyses reveal three kinds of interactions among the T-box genes: combinatorial interactions that generate new regulatory functions, additive contributions to common developmental pathways, and competitive antagonism governing downstream gene expression. We propose that T-box genes, like Hox genes, often function within gene networks comprised of related family members.